KANDUNGAN KOPI KEDELAI LAUWON KECAMATAN LUWUK TIMUR KABUPATEN BANGGAI - Ramadhani Chaniago; Bakri Muala (Universitas Muhammadiyah Mataram, 2020)
Soybean is an ingredient that has many benefits and is informed that it does not contain caffeine, so it is good and safe for consumption by children, pregnant women, and people who have digestive diseases. This study aims to determine the content of soy coffee produced by the people of Lauwon Village, East Luwuk District, Banggai Regency, Central Sulawesi Province. This research was conducted from April to August 2020 which consisted of 2 stages, namely: 1) the first stage, the manufacture of soy coffee which was carried out by the people of Lauwon Village, Luwuk Timur District, Banggai Regency, Central Sulawesi Province. 2) the second stage, laboratory testing at the Integrated Research and Testing Laboratory (LPPT) UGM Yogyakarta. The results showed that Lauwon soybean coffee does not contain caffeine (non-caffeine) and contains water content (3.42%), protein (31.26%), total fat (0.95%), total sugar (0.50%). ), lead (Pb) was not detected, copper (Cu) (13.97 mg / kg), zinc (Zn) (52.99 mg / kg), mercury (Hg) 0.04 mg / kg, bacterial contamination rate ( ALT) 2.0 x 103 cfu / gram and DPPH free radical scavenging activity (IC50) 2.467 mg / mL.